(untitled) (Global Journal of Medical Research, 2023)
In order to discuss the postoperative complications of Ilizarov technique in the treatment of neurogenic talipes equinovarus, we conducted a retrospective study on the postoperative complications of neurogenic talipes equinovarus patients treated with Ilizarov technique from January 2013 to December 2020. 182 patients (228 feet), 134 males (171 feet) and 48 females (57 feet). The age ranged from 4 to 70 (¯x23.6 ± 13.9) years old. There were 44 cases of sequelae of cerebral palsy (24.2%), 112 cases of sequelae of poliomyelitis (61.5%), 18 cases of congenital horseshoe foot (9.9%), and 8 cases of traumatic horseshoe foot (4.4%). The postoperative curative effect was evaluated, and the types of complications and their correlation with age were statistically analyzed. According to ICFSG score, the excellent and good rate of this group was 89.04%.